Platypnea-orthodeoxia syndrome related to right hemidiaphragmatic elevation and a ‘stretched’ patent foramen ovale - Sakagianni, Katerina (BMJ Case Rep, 2012)
Patent foramen ovale (PFO), although frequently observed in adults, rarely causes adverse clinical consequences. The most serious among them, are cryptogenic strokes and less commonly significant hypoxia resulting from right-to-left shunt (RLS). Platypnea-orthodeoxia syndrome referring to abnormal oxygenation in the upright position has been correlated with reopening of foramen ovale and acute right-to-left intracardiac shunt. We report a case of platypnea-orthodeoxia syndrome secondary to the development of RLS through a ‘stretched’ PFO, in a patient admitted to the intensive care unit with severe respiratory failure requiring mechanical ventilation. The RLS was associated with right hemidiaphragmatic elevation, without an increased interatrial pressure gradient. The patient was successfully weaned from the ventilator after the percutaneous closure of PFO through a catheter-deployed double-umbrella device, presenting a full recovery.